Sensitivity Analysis with Respect to the Electrical Conductivity (Journal of Computational Mathematics, 2007)
In this paper, we consider conductivity inclusions inside a homogeneous background conductor. We provide a complete asymptotic expansion of the solution of such problems in terms of small variations in the electrical conductivity of the inclusion. Our method is based on a boundary integral perturbation theory. Our results are valid for both high and low contrast inclusions.